PENGARUH MENTAL ACCOUNTING DAN FINANCIAL BEHAVIOR TERHADAP FINANCIAL SATISFACTION - Istisqa, Fatra; Sartika, Novira (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the influence of mental accounting and financial behavior on financial satisfaction among lecturers in Bengkalis Island. The research employs a quantitative approach using cross-sectional survey method. The population comprises all active lecturers in educational institutions on Bengkalis Island, with a sample of 207 respondents selected through convenience sampling. Data were collected using an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS version 4.0. The findings indicate that mental accounting has a positive and significant effect on financial satisfaction with a coefficient of 0.137 and p-value of 0.045. Financial behavior also demonstrates a positive and significant influence with a stronger coefficient of 0.182 and p-value of 0.005. Both variables collectively explain only 5.4 percent of the variation in financial satisfaction, suggesting that numerous other factors influence financial satisfaction. The study concludes that structured financial management through mental accounting and healthy financial behavior are important components for enhancing individual financial satisfaction, although their contribution remains limited and requires integration with other factors such as financial literacy and emotional intelligence.